Review paperDoctor – public officer? - Jakubowicz, Jędrzej; Jakubowicz, Oliwia; Żaba, Czesław; Żaba, Ryszard; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
This paper presents themes regarding cases in which the doctor is considered as a public officer. However, a distinction is made between a doctor as a public officer, and a doctor as a person performing a public function.